GAMA Arabic (Arabic Listening Games) Based on Intercultural Education for Skills Listening to Arabic - Kusumadewi, Novita; Fajar Nurizki, Aziz; Nabila Amjad, Khaulah; Zukhaira, Zukhaira; Jamil, Jamat (Jurnal Penelitian Pendidikan, 2019)
Arabic in Indonesia is one of the foreign languages studied in formal and non-formal education institutions ranging from MI / SD, MTs / SMP, MA / SMA, to college level. When studying the language of a country, not separated to learn the culture. Intercultural education is a process whereby the broader cultural insights of learners, with the help of new information on other cultures and languages / languages and at the same time, raise children's awareness of their own cultural and language specific features (Madya, 2013: 194). Arabic learning can be successful if students have mastered four language skills (Iskandarwassid 2011: 226). These four skills include listening (mahaarah al-istima), speaking (mahaarah al-takallum), reading (mahaarah al-qira'ah), and writing (mahaarah al-Kitaabah). Language learning should be carried out hierarchically from listening skills to writing skills (Tarigan 1993: 34). Although learning Arabic in Indonesia has been going on for centuries, learning skills listening and speaking Arabic still lack sufficient attention and focus. Based on the above problems required a solution in the form of a variety of learning media that can be utilized by teachers and students in learning listening that is GAMA Arabic, a Game Listening Arabic in which not only teach and train related listening skills, but the content of education-based materials intercultural remembering to learn the language will not be apart from learning the language culture.Â Â